Short enantioselective total synthesis of (+)-tofacitinib - Mane, Kishor D.; Kamble, Rohit B.; Suryavanshi, Gurunath (Tetrahedron Letters, 2021)
An enantioselective total synthesis of Tofacitinib (CP-690,550), a Janus tyrosine kinase (JAK3) specific inhibitor has been achieved from the readily available 4-piperidone. Proline catalysed hydroxylation is the key step for the synthesis of enantiopure 1-benzyl-4-methylpiperidin-3-ol. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: aminohydroxylation; Hydrogenation; L-proline; piperidone

Synthesis of 3 alkyl and 1,3-Bis(alkyl)indolizine amides from a-bromohydroxamates - Mane, Kishor D.; Bagwe, Sagar S.; More, Satish G.; Suryavanshi, Gurunath (Tetrahedron Letters, 2023)
A simple and catalyst-free method has been developed for the synthesis of hindered indolizine amide derivatives from functionalized alkyl bromides. The reaction of a variety of indolizine derivatives with azaoxyallyl cations generated in situ from a-bromoamides afforded a wide range of synthetically important mono- and di-alkylated indolizine amide derivatives in good to excellent yields.@2023 Elsevier Ltd. All rights reserved.
Keywords: a -Bromohydroxamates; Amides; HFIP; Indolizine